New Model of Ventral Spinal Cord Lesion Induced by Balloon Compression in Rats - Krupa, Petr; Stepankova, Katerina; Kwok, Jessica Cf; Fawcett, James W; Cimermanova, Veronika; Jendelova, Pavla; Machová Urdzíková, Lucia (Biomedicines, 2020)
Despite the variety of experimental models of spinal cord injury (SCI) currently used, the model of the ventral compression cord injury, which is commonly seen in humans, is very limited. Ventral balloon compression injury reflects the common anatomical mechanism of a human lesion and has the advantage of grading the injury severity by controlling the inflated volume of the balloon. In this study, ventral compression of the SCI was performed by the anterior epidural placement of the balloon of a 2F Fogarty's catheter, via laminectomy, at the level of T10. The balloon was rapidly inflated with 10 or 15 μL of saline and rested in situ for 5 min. The severity of the lesion was assessed by behavioral and immunohistochemical tests. Compression with the volume of 15 μL resulted in severe motor and sensory deficits represented by the complete inability to move across a horizontal ladder, a final Basso, Beattie and Bresnahan (BBB) score of 7.4 and a decreased withdrawal time in the plantar test (11.6 s). Histology and immunohistochemistry revealed a significant loss of white and gray matter with a loss of motoneuron, and an increased size of astrogliosis. An inflation volume of 10 μL resulted in a mild transient deficit. There are no other balloon compression models of ventral spinal cord injury. This study provided and validated a novel, easily replicable model of the ventral compression SCI, introduced by an inflated balloon of Fogarty ́s catheter. For a severe incomplete deficit, an inflated volume should be maintained at 15 μL.